Three-Dimensional Brain Images in Preterm Children With Periventricular Leukomalacia - Hsiao-Feng Chou; Ming-Fan Lin; Chia-Yuan Chen; Ein-Yiao Shen (Elsevier, 2012)
To investigate the use of three-dimensional (3D) brain magnetic resonance imaging (MRI) to evaluate in preterm children with periventricular leukomalacia. Materials and Methods: Semiautomated 3D classification of the gray and white tissues was used to reconstruct brain images of patients with confirmed periventricular leukomalacia from 2D MRI. Results: We studied 14 preterm patients. The gestational age ranged from 25-37 weeks. The corrected age ranged from 5-49 months. We reconstructed the gray matter, white matter, and ventricles in order to analyze the brain volume. Conclusion: Three-dimensional MRI is a good tool that can be used to demonstrate brain lesions in stereo and differentiate the gray matter, white matter, and ventricles. Brain volume can also be accurately evaluated.